Federal Spending on Social Assistance Programs in Brazil - World Bank (World Bank, Washington, DC, 2021)
The development of Brazil’s modern social safety net is quite recent, and social assistance programs claim a relatively small share of resources of the broader social sector. A key feature of the Brazilian social protection system is the duality between formal sector workers, who gained social insurance and labor benefits as early as the 1930s, and the large number of mostly poor informal workers and their families who were historically excluded. The objective of social assistance programs in Brazil is to provide support to people living in poverty and other vulnerable groups. These programs primarily include social pensions for the poor elderly and disabled, conditional cash transfers for poor families, unconditional cash transfers, housing assistance for low-income households, school feeding, food programs, social services, and a variety of other small benefits and services. They are usually targeted to the poor or low-income groups via means-testing, or provide eligibility to specific vulnerable groups. Within the broader system of social protection, social assistance programs complement social insurance pensions, which are contributory by design but have been significantly subsidized from general taxation, and labor market programs, which are largely contributory and include a mix of active and passive benefits and services. The current note focuses on Social Assistance Programs while a second background chapter focuses on Labor market programs. This document is a Background Chapter for the report A fair adjustment : efficiency and equity of public spending in Brazil : Volume 1 - Overview (report No.121480).